Determination of Mechanical Properties of Aged NPP Components Using Instrumented Hardness Testing and Other Miniature Specimen Testing Techniques - Lenkey, G.B.; Szavai, Sz.; Rozsahcgyi, P.; Koves, T.; Jonas, Sz.; Beleznai, R. (Проблемы прочности, 2013)
Analyses of instrumented hardness test and small punch test are done using experimental tests and finite element simulation. These methods can be used when some material properties are unknown and there is no way to cut larger pieces from the structure to determine them using standard size specimens. С использованием экспериментальных данных и конечноэлементного моделирования анализируются экспериментальные методы инструментальной оценки твердости и индентирования малых образцов. Данные методы можно использовать при определении некоторых
неизвестных механических свойств материала, когда нет возможности вырезать образцы
стандартных размеров из исследуемой конструкции. Із використанням експериментальних даних і скінченноелементного моделювання аналізуються експериментальні методи інструментальної оцінки твердості й індентування малих зразків. Дані методи можна використовувати при
визначенні деяких невідомих механічних властивостей матеріалу, коли немає
можливості вирізати зразки стандартних розмірів із досліджуваної конструкції.